2013
DOI: 10.1074/mcp.m112.022772
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptome-proteome Integrated Network Identifies Endoplasmic Reticulum thiol oxidoreductase (ERp57) as a Hub that Mediates Bone Metastasis

Abstract: Bone metastasis is the most common distant relapse in breast cancer. The identification of key proteins involved in the osteotropic phenotype would represent a major step toward the development of new prognostic markers and therapeutic improvements. The aim of this study was to characterize functional phenotypes that favor bone metastasis in human breast cancer. We used the human breast cancer cell line MDA-MB-231 and its osteotropic BO2 subclone to identify crucial proteins in bone metastatic growth. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 73 publications
(55 reference statements)
2
22
1
3
Order By: Relevance
“…Notably, the expression levels of EMT-associated proteins MMP1, MMP2, MMP9 and vimentin were lower in SKOV3/tax cells than that in SKOV3 cells, suggesting that SKOV3/tax cells exhibited less metastasis than SKOV3 cells. In the present study, ERp57 was highly expressed in less metastatic cells (SKOV3/tax), which was not in agreement with Naiara's observation that overexpression ERp57 was related to bone metastasis in breast cancer cell (53).…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, the expression levels of EMT-associated proteins MMP1, MMP2, MMP9 and vimentin were lower in SKOV3/tax cells than that in SKOV3 cells, suggesting that SKOV3/tax cells exhibited less metastasis than SKOV3 cells. In the present study, ERp57 was highly expressed in less metastatic cells (SKOV3/tax), which was not in agreement with Naiara's observation that overexpression ERp57 was related to bone metastasis in breast cancer cell (53).…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, Pdia3 was highly expressed in cervical cancer patients, and knockdown of Pdia3 led to decreased cell invasiveness both in vivo and in vitro . Furthermore, Pdia3 promotes the development of bone metastasis in breast cancer . In the present study, we found that knockdown of Pdia3 expression inhibited proliferation and migration of mouse keratinocytes.…”
Section: Discussionsupporting
confidence: 55%
“…Of related interest, depletion of PDIA3 in MDA-MB-231 breast cancer cells reduced chemoresistance-associated proliferation [ 23 ]. In vitro , differential transcriptome and proteome analyses of the bone metastasis-prone MDA-MB-231-BO2 breast cancer cell line versus parental MDA-MB-231 cells identified PDIA3 as a mediator of bone metastasis-associated proteins [ 24 ]. PDIA3 was also shown to be involved in EGF receptor signalling in MDA-MB-468 breast cancer cells [ 25 ] and to promote growth of SUM159PT mammosphere cultures [ 26 ].…”
Section: Introductionmentioning
confidence: 99%